Small-Strain Shear Modulus and Strength Characteristics of Clayey Soil Treated with Nano-SiO2 and Fly Ash - Munda J.; Ram A.K.; Mohanty S. (My University, 2025)
The study investigated the enhancement of mechanical strength and small-strain stiffness characteristics of soil blended with Nano-SiO2 and fly ash. Through consistency limits, compaction, unconfined compression strength (UCS), and triaxial testing (UU), the fundamental characteristics of the specimens were evaluated. A series of piezoelectric bender element tests were performed at various confining pressures (50 kPa, 100 kPa, and 150 kPa) to measure the small-strain shear modulus (Gmax) of the soil matrix. For a better understanding of the underlying microstructural changes found in the specimens, the Energy dispersive X-ray spectroscopy (EDS) analysis and Scanning Electron Microscopy (SEM) investigation were both conducted. With curing ages of 1, 7, 14, and 28 days, five distinct combinations of Nano-SiO2 (0.5%, 1%, 3%, 5%, and 7%) and fly ash (10%, 20%, and 30%) by weight of soil were used in this investigation. After 28 days, the rate of increase in UCS and shear strength of 1% Nano-SiO2 treated soil was found to be 97.12% and 215.04%, respectively. The soil treated with 1% Nano-SiO2 and 20% fly ash increased the shear strength by 295% after 28 days of curing. At 28 days of curing age, the treated soil's optimal composition of 1% Nano-SiO2 and 20% fly ash produced the maximum strength and shear stiffness. An exponential correlation was developed between small-strain shear stiffness and shear strength for the composite mix. The correlation may help in predicting the small-strain shear modulus of the clayey soil treated with the optimized Nano-SiO2 and fly ash using triaxial tests. © 2023, The Author(s), under exclusive licence to the Iran University of Science and Technology.